People with epilepsy have poor life satisfaction and self-rated health: Findings from the United Kingdom - Kang, Weixi (Frontiers in Psychology, 2023)
Epilepsy is a neurological disorder characterized by brief, recurrent disturbances in the normal electrical functions of the brain that result in seizures. Although epilepsy is closely related to well-being, much less is known about how life satisfaction and SRH are affected by epilepsy in a nationally representative sample from the United Kingdom. The current research aims to investigate the difference in life satisfaction and SRH between people with epilepsy and people without epilepsy by using an innovative train-and-test approach on data collected between 2009-2010 from 428 people with epilepsy and 39, 024 healthy controls while taking demographics into account. The results showed that people with epilepsy have both poorer life satisfaction and SRH compared to the scores that would be predicted by their demographics. This study implies that both life satisfaction and SRH are valid measures of well-being in people with epilepsy. Health professionals may utilize findings from the current study to come up with ways that can benefit well-being of people with epilepsy.